2007
DOI: 10.1055/s-2007-962881
|View full text |Cite
|
Sign up to set email alerts
|

Best Duplex-Sonographic Criteria for the Assessment of Renal Artery Stenosis - Correlation with Intra- Arterial Pressure Gradient

Abstract: DS measurements and the severity of arteriographic diameter reduction correlate well with systolic pressure gradients. Clinically expedient DS criteria for detecting RAS of > or = 50 % are a PSV of > or = 200 cm/sec or a RAR of > or =2.5. These criteria allow reliable exclusion of severe RAS of > or = 70 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 15 publications
5
58
0
5
Order By: Relevance
“…However, this criterion is not commonly used in our practice. Unlike obstructive uropathy [40,41], the abnormal kidney will show reduced RIs beyond the point of stenosis [42].…”
Section: Distal Criteria (Indirect Evaluation Of the Stenosis)mentioning
confidence: 99%
“…However, this criterion is not commonly used in our practice. Unlike obstructive uropathy [40,41], the abnormal kidney will show reduced RIs beyond the point of stenosis [42].…”
Section: Distal Criteria (Indirect Evaluation Of the Stenosis)mentioning
confidence: 99%
“…Staub et al [29] found in 49 retrospectively analyzed patients a good correlation between duplex sonography measurements and the severity of arteriographic diameter reduction with systolic pressure gradients. The clinically expedient duplex sonography criteria for detecting RAS of ≥ 50 % are a PSV of ≥ 200 cm/sec or an RAR of ≥ 2.5.…”
Section: Discussionmentioning
confidence: 99%
“…Before intervention, duplex ultrasound was always confirmed by intra-arterial angiography showing a percent diameter stenosis ≥50% by measuring the ratio between the diameter of the narrowest segment of the imaged renal artery and the diameter of a normal segment of the artery proximal to the stenosis or distal to poststenotic dilation. Alternatively, an intra-arterial, trans-lesional systolic pressure gradient of ≥20 mmHg was considered as hemodynamically relevant and was assessed in 31 patients (6). A RAS ≥70% was documented in 84% of all patients and mean systolic pressure gradient was 72±46 mmHg.…”
Section: Patient Populationmentioning
confidence: 99%
“…Assessment of RAS was based primarily on duplex ultrasound using a Philips ATL, HDI 5000 (Philips, Best, Netherlands). As described previously, RAS was classified as hemodynamically relevant if the renal/aortal velocity ratio was ≥2.5 (6). For unilateral RAS the side-to-side difference in intrarenal RI =1-[end-diastolic velocity/peak systolic velocity] between the 2 kidneys >0.05 was also used to classify hemodynamically relevant RAS.…”
Section: Patient Populationmentioning
confidence: 99%